Accountable for Care: Cultivating Caring School Communities in Urban High Schools. Issue 4 (1st October 2016) - Tichnor-Wagner, Ariel; Allen, Danielle
ABSTRACT: This comparative case study examines the prevalence of caring practices in two higher performing and two lower performing urban high schools and the contextual factors that helped or hindered the extent to which students felt cared for. We found that higher performing schools demonstrated caring communities, where interpersonal relationships and high academic expectations were prevalent throughout the school. Strong leadership support, caring as a core school value, and abundant curricular and extracurricular structures facilitated relationships in caring school communities; these contextual factors were less prevalent in lower performing schools with isolated instances of care. Implications for school leaders are discussed.